Revisiting Signatures of Thermal Axions in Nonstandard Cosmologies - Venegas-M, H; Arias-Reyes, P (American Physical Society, 2024)
We revisit the formation of a thermal population of hadronic axions in nonstandard cosmologies, in light of the recent developments in obtaining continuous and smooth interaction rates for both the gluon and photon couplings. For certain cosmological histories, such as low-temperature reheating (LTR) and kinationlike scenarios, the thermalization of the axion can be severely delayed to higher masses. In the case that thermal equilibrium is achieved, we improve the constraints on LTR for axion masses around the eV scale with respect to previous works and we constrain for the first time early matter-dominated cosmologies. We also point out the possibility of having the coexistence of cold and warm dark matter populations of axions in kinationlike scenarios in the eV mass range. © 2024 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the "https://creativecommons.org/licenses/by/4.0/"Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article s title, journal citation, and DOI. Funded by SCOAP3